2015
DOI: 10.1021/jacs.5b01894
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Determination of the Leupyrrins and Total Synthesis of Leupyrrin A1

Abstract: The stereochemical determination of the potent antifungal agents leupyrrin A1 and B1 and the total synthesis of leupyrrin A1 are reported. The relative and absolute configuration was determined by a combination of high field NMR studies, molecular modeling, and chemical derivatization. The expedient total synthesis involves a one-pot sequential Zr-mediated oxidative diyne-cyclization/regioselective opening sequence for preparation of the unique dihydrofuran ring, a highly stereoselective one-pot approach to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…This would provide two complementary routes to substituted 2-oxazolines, which are valuable heterocycles found in ligand scaffolds, natural products such as the leupyrrins [1819], and potential pharmaceuticals (Fig. 1) [2022].…”
Section: Introductionmentioning
confidence: 99%
“…This would provide two complementary routes to substituted 2-oxazolines, which are valuable heterocycles found in ligand scaffolds, natural products such as the leupyrrins [1819], and potential pharmaceuticals (Fig. 1) [2022].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] derivatives. We synthesized new 4-methyl-2-(2-vinylstyryl)oxazole (1), 4-methyl-5-(2-vinylstyryl)oxazole (2), 2-methyl-4-(2-vinylstyryl)oxazole (3), and 2-phenyl-5-(2-vinylstyryl)oxazole (4). [8] There are various methodologies and synthetic approaches for the synthesis of the oxazole ring incorporated into diverse skeletons [9] because the oxazole structure is commonly found in a vast number of natural products and pharmaceuticals.…”
Section: 1]octenonementioning
confidence: 99%
“…The study of the 5-tolyl-, 4,5-diphenyland 4-phenyl-5-methyl-2-(2-vinylstyryl)oxazole showed that the phenyl substituent on the 4-position in the oxazole ring has a high impact on the overall electron density distribution in the molecule and on the photocyclization process (Scheme 1). [2] New routes to oxazoline derivatives are more than welcome because of the presence of the oxazoline ring in ligand scaffolds, natural products [3,4] and potential pharmaceuticals. The oxo-bridged photoproducts E could further be easily converted into benzo[f ]qouinolines (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…These structures also contain ap yrrole, an oxazoline, and ad iacid fragment as additional characteristic features together with aside chain that is attached to the oxazoline moiety. [8] Leupyrrin A 1 has demonstrated highly potent antifungal properties against Rhodotorula glutinis, Aspergillus niger, Botrytis cinerea,a nd Mucorh iemalis with minimum inhibitory concentration( MIC) values in the submicromolar range and antiproliferative activities against mousef ibroblast cells. They contain up to seven stereogenic centers,w hich have been recently assigned in our group by extensive NMR studies in combination with molecular modeling and chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[8,10,11] Here, we describe, in full detail,t he design, evaluation and elaborationo ft he variouss ynthetic tactics that we pursued to access the unique three-dimensional architecture of the leupyrrins. [8,10,11] Here, we describe, in full detail,t he design, evaluation and elaborationo ft he variouss ynthetic tactics that we pursued to access the unique three-dimensional architecture of the leupyrrins.…”
Section: Introductionmentioning
confidence: 99%